Improvement of output voltage from shading interference on solar cell using a reflector system - Muhammad Iqbal; Eko Ihsanto; Agab Bakheet Mohammednour (Asosiasi Staf Akademik Perguruan Tinggi Seluruh Indonesia (ASASI), 2022)
One of the factors that affect the performance of photovoltaic cells is shading. Shading can reduce the intensity of solar radiation on the cells. This study aims to design a system that can improve the amount of voltage from shading disturbances to optimise the output voltage on the solar cell by using a reflector. The reflector is designed in a flat mirror measuring. It is expected that there will be an increase in the output voltage of the existing solar cell system. The more reflected light that hits the surface of the solar panel and illuminates the shading area, the more significant the increase in output voltage, current and power, and vice versa.